2022
DOI: 10.2147/jaa.s345427
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Allergic Bronchopulmonary Aspergillosis: A Retrospective Cohort Study

Abstract: Background:The clinical features, treatment, and prognosis of allergic bronchopulmonary aspergillosis (ABPA) are not well-defined. Objective: We aimed to investigate the clinical characteristics, therapy, and prognosis of ABPA to aid its clinical recognition. Methods: A total of 232 patients with ABPA were analyzed retrospectively. The characteristics of ABPA in terms of its misdiagnosis, computed tomography classification, therapy, and its relationship with asthma were analyzed, and risk factors for acute exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…Smoking history was closely associated with genesis and development of COPD and worse pulmonary function, which was also demonstrated in this study. Although a retrospective study found that DLCO/VA was lower in patients who had ABPA with CB, 18 CB had no significant association with DLCO/VA in this study. Thus, the important factor leading to the decline in pulmonary ventilation and diffusing capacity in our patients was coexisting COPD, and not CB.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Smoking history was closely associated with genesis and development of COPD and worse pulmonary function, which was also demonstrated in this study. Although a retrospective study found that DLCO/VA was lower in patients who had ABPA with CB, 18 CB had no significant association with DLCO/VA in this study. Thus, the important factor leading to the decline in pulmonary ventilation and diffusing capacity in our patients was coexisting COPD, and not CB.…”
Section: Discussioncontrasting
confidence: 86%
“…31 In another study, 1 out of 46 patients with ABPA had COPD, 32 and in a recent retrospective analysis by Zeng, 3 out of 193 patients with ABPA had COPD. 18 It can be speculated that a large number of patients with COPD and ABPA are underdiagnosed or misdiagnosed, leading to a higher age at the time of first diagnosis in these patients. These two aspects lead to the fact that the age of patients with ABPA and COPD is much higher than that of ABPA patients without COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In susceptible hosts (mainly patients with asthma or cystic fibrosis), repeated inhalation of A. fumigatus spores, followed by respiratory tract colonization, triggers an immune hypersensitivity reaction [ 21 ]. This reaction is mediated by an immunoglobulin E (IgE), with possible involvement of immunoglobulin G (IgG)-mediated immune complex and cell-mediated hypersensitivity reactions [ 22 , 23 ].…”
Section: Allergic Fungal Diseasesmentioning
confidence: 99%
“…The clinical manifestations include chronic asthma or bronchiectasis and recurrent wandering pulmonary shadows or mucus blockage in lung images ( 6 ). While ABPA was mostly found in patients with bronchial asthma or cystic fibrosis in Western countries, it was more common in patients with asthma and bronchiectasis in China ( 7 ). A study revealed that the estimated prevalence of ABPA in adults with asthma was at 2.5% ( 8 ) and could rise up to 45% in patients with A.f -sensitized asthma ( 9 ).…”
Section: Introductionmentioning
confidence: 99%